Fractionation of the antibacterial components of citrus aurantifolia swingle (Fam. Rutaceae) fruit extracts - Avestruz. Vincent Anthony E.
In the Philippines, the use of herbal medicine as remedy for diseases are still common: among theses herbal medicines is Citrus aurantifolia. Previous studies have shown that the fruit extracts of C. aurantifolia exhibits antibacterial property. Therefore, the study aimed to isolate and characterize the fractions responsible for the antibacterial activity of C. aurantifolia extracts through fractionation via modified Kupehan method, photochemical screening, antimicrobial testing using agar plate diffusion, agar dilution assay and TLC bioautography, and to establish a TLC profile of the extract. Obtained results have shown that plant acids, glycosides and flavonoids are present in the fruit extract. Upon fractionation and antimicrobial testing, it was found that the ethyl acetate fraction (1 mg/disc) exhibited the greatest antibacterial property with greater activity against gram-positive bacteria (B. suntilis and S.aureus) than gram-negative bacteria (E. coli and P. vulgaris). The Minimum Inhibitory Concentration (MIC) of the thyl acetate fraction is more than 1mg as deduced from the agar dilution assay. The thin layer chromatography optimization of the crude extract and ethyl acetate led to the use of ethyl acetate: n-hexane: glacial acetic acid (5:4:1) as the appropriate solvent system for both the TLC of C. aurantifolia crude extract ans ethyl acetate fraction. Results from the bioautography have shown that the zones of inhibition in the B.subtilis culture were around the spots near the solvent front and small zones of inhibition can also be observed for the S. aureus culture. This suggests that the compound responsible for the antimicrobial activity is most likely a mi-polar flavonoids.